Will Sirtuin 2 Be a Promising Target for Neuroinflammatory Disorders? - Fan, Zhang; Bin, Li (Frontiers in Cellular Neuroscience, 2022)
Neuroinflammatory disorders referred to a type of disease that associated with the progressive loss of neuronal structure or function. And neuroinflammation is the biggest accomplice of neurodegenerative diseases. Apart from the symptomatic treatment with cholinesterase inhibitors, antidepressants/anxiolytics and neuroprotective drugs, the treatment of neuroinflammation is an important therapeutic method. Sirtuins are a host of class III of histone deacetylases, which require nicotinamide adenine dinucleotide for their lysine residue deacetylase activity. The role of SIRT2, one of Sirtuins, in modulating the senescence, myelin formation, autophagy, and inflammation has been widely studied. SIRT2 is associated with many neuroinflammatory disorders by its deacetylation characteristic to regulate the entire immune system. At present, the widely studied diseases with neuroinflammatory components included Alzheimer’s disease, Parkinson’s disease, Depression, Stroke, and so on. The aim of this review is to summarize the latest progress about the regulating effects of SIRT2 on immune system in neuroinflammatory disorders. This article elaborated the overall structure and catalytic properties of SIRT2, the selective inhibitors of SIRT2, the relationship between immune system and SIRT2, and the multitasking role of SIRT2 in several diseases with neuroinflammatory components. Taken together, such valuable information implies that SIRT2 serve as a promising therapeutic target for the treatment of neuroinflammatory disorders.